Media Control On Corruption In Local Goverment ; Create Clean And Justice Government In South Sulawesi Province (Analysis of the Role of the Media in the Era of Regional Autonomy) - Cangara, Hafied; Amir, Subhan; Arya, Nosakros (Advances in Social Sciences Research Journal, 2020)
This study aims to determine the role of community newspaper in carrying out its oversight function of corruption in South Sulawesi province, Indonesia. The type of research used is the content analysis and in-depth interviews with several key informants, including the mayor, the attorney general, the police, non-governmental organizations, and newspaper publishers. The unit of analysis is four local newspapers namely Pare Pos, Palopo Pos, Radar Bone and Radar Selatan. These four newspapers were published outside the provincial capital of South Sulawesi, Makassar. Data analysis used the Single Factor Analysis of variance (ANOVA) or one-factor ANOVA (One Way ANOVA) test. The findings of the study show that: (1) the media has a role in carrying out its oversight function of corruption in government institutions in South Sulawesi, although this is not solely because of the media, but also the regulation and supervision carried out by the government through the bureaucratic path, (2) The portion of community newspaper coverage of corruption is quite large compared to other themes. However, judging from the tone of the news in general, it is still nuanced with information, and there has not been much investigated reporting. (3) Judging from the frequency of the coverage of these four newspapers, the Palopo Pos Daily and Radar Bone Daily showed a trend in reporting corruption issues, while the Pare Pos and Radar Selatan Daily tended to focus more on public service issues, for example waste, road, drinking water, electricity and traffic problems. However, statistical analysis showed that the difference was not significant.